Evapotranspiração e produção de melancia sob diferentes níveis de nitrogênio e da salinidade da água de irrigação - Silva, José Silereudo da (2010)
Water is one of the main factors that limit agricultural yield, consequently reducing the efficiency of crop production. It makes necessary then a special management of irrigation that allows total capacity of production. This way, to implement strategic programs of local or regional development of agriculture based on the availability of water resources it is essential to have a good understanding of crop evapotranspiration on its different stages of development as well as of the quality of the water used in the irrigation process. In the northeast, due to water shortages many farmers are forced to use water containing high levels of salinity what reduces the production in crops with low tolerance to salinity. So, the main objective in this study is to determine the production coefficients during the watermelon production period, in the region of Mossoró city in the State of Rio Grande do Norte, Brazil, and the effect of nitrogen and salinity on watermelon production. Therefore an experiment was carried out in Mossoró city. The experiment was in a randomized block design in which was used a plan of subdivided parts. In these parts it was studied five levels of salinity (S1 = 0,57; S2 = 1,36; S3 = 2,77; S4 = 3,86 e S5 = 4,91 dS m-1) and three levels of nitrogen in subparts (N1 = 48,0; N2 = 96,0 e N3 = 144,0 kg ha-1). For the ETo estimate it was used the Penman Equation Monteith FAO. The meteorological data necessary for this ETo estimate were collected by an agrometeorological automatic weather station, located on the experimental area. The ET was measured by four weighting lisimeters, which covered an area of 3,00 m2 and were installed in blocks 1 and 2, in the salinity levels S1 and S5. The results have demonstrated that the ETc diminished between the irrigation water S1 and S5, and the total evapotranspiration during the cycle was 336,86 and 220,45 mm respectively. It was realized that the average values referring to Kc in the fenological stages I, II, III and IV of 0,15, 0,87, 1,38 and 0,82 for treatment S1 and 0,15, 0,65, 08,3 and 0,51 for treatment S5, demonstrating that the Kc s obtained for level S1 were higher than the ones obtained for level S5, except for stage I. There was an expressive effect of nitrogen on the production components. The total production of fruit for Quetzali cultivar as much as for Shadow cultivar were severely affected by the quality of irrigation water. For the Quetzali cultivar the total production was reduced from 27,12 to 17,06 Mg ha-1. While for the Shadow cultivar it was reduced from 55,45 to 40,80 Mg ha-1, respectively for the salinity levels S1 and S5.